Wnt Signaling in 3D: Recent Advances in the Applications of Intestinal Organoids - Merenda, Alessandra; Fenderico, Nicola; Maurice, Madelon M. (Elsevier Limited, 2020)
Intestinal organoids grown from adult stem cells have emerged as prototype 3D organotypic models for studying tissue renewal and homeostasis. Owing to their strict dependence on Wnt signaling, intestinal organoids offer an unprecedented opportunity to examine Wnt pathway regulation in normal physiology and cancer. We review how alterations in growth factor dependency and organoid morphology can be exploited to identify Wnt signaling mechanisms, characterize mutated pathway components, and predict responses of patient-derived tumors to targeted therapy. We discuss current deficits in the understanding of genotype–phenotype relationships that are to be considered when interpreting mutation-induced changes in organoid morphology.
Keywords: applications; intestinal organoids; mutations; organoid morphology; Wnt pathway; Cell Biology; Review; Journal Article